From International to World Society? : English School Theory and the Social Structure of Globalisation - Buzan, Barry (Cambridge : Cambridge University Press, 2004)
Offers a critique and revision of English school theory and sets out a new theoretical framework.
Introduction; 1. English school theory and its problems: an overview; 2. World society in English school theory; 3. Concepts of world society outside the English school; 4. Reimagining the English school's triad; 5. Reconstructing the pluralist-solidarist debate; 6. The primary institutions of international society; 7. Bringing geography back in; 8. Conclusions: a portrait of contemporary interstate society.
Keywords: Globalization -- Sociological aspects